Sosialisasi Pemanfaatan Pembangkit Listrik Tenaga Surya (PLTS) Di Desa Tawa Kabupaten Halmahera Selatan - Muhammad Yunus H Abbas; Endah Harisun; Iis Hamsir Ayub Wahab; Acmad P. Sardju (Journal Of Khairun Community Services, 2021)
One of the methods used for the provision of electricity used en masse is the Photovoltaic Solar Energy system (SESF) or better known as Photovoltaic Solar Power Plant. Tawa Village which is one of the remote villages in South Halmehera Regency has not been reachable by electricity sources from PLN. As one of the villages affected by the 7.2 richter scale earthquake in July 2019, Tawa Village relies solely on Photovoltaic Power Plant for its village lighting. With limited power that is the capacity of solar panels 50 Wp, plts can only serve the needs of electricity at night and during the day there is no supply of electricity. This form of socialization is direct socialization where direct socialization is direct communication in the form of face-to-face communication between the two parties, namely communicators and communion. Â In this socialization who acts as a communicator is the father of M.Yunus Hi. Abbas, ST.,MT lecturer of Elector Engineering Study Program, Faculty of Engineering, Khairun University and his communion are all citizens of Tawa village. socialization activities utilization of Solar Power Plants (PLTS) in Tawa Village, it is expected that the public can understand the utilization of Solar Power Plants properly and know the stages of solar panel maintenance so as to produce solar energy sources that will be channeled into electricity that can serve household needs such as lighting lamps, televisions, radios, fans and other household needs